2007
DOI: 10.1111/j.1471-0528.2007.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

Tibolone and low‐dose continuous combined hormone treatment: vaginal bleeding pattern, efficacy and tolerability

Abstract: ObjectivesThe primary objective was to compare the vaginal bleeding pattern during administration of tibolone and low-dose continuous combined estradiol plus norethisterone acetate (E 2 / NETA). The secondary objectives were efficacy on vasomotor symptoms and vaginal atrophy.Design A randomised, double-blind, double-dummy, group comparative intervention trial.Setting Multicentre study executed in 32 centres in 7 European countries.Sample Five hundred and seventy-two healthy symptomatic postmenopausal women, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 40 publications
2
44
0
1
Order By: Relevance
“…For example, results from one study that compared the bleeding profiles of high-and lowdose combinations of HT showed cumulative amenorrhea rates that were lower compared with placebo at all time points for up to 1 year with all dose combinations (25), as similarly shown in previous reports (29). In a study comparing tibolone versus low-dose continuous combined E 2 plus norethisterone acetate (26), bleeding rates of 18.3% and 33.1%, respectively, during the first 3-month interval of treatment decreased to 11.4% and 19.9%, respectively, during the interval from month 7 through 9. Bleeding profiles associated with other nontraditional HT approaches may not be as favorable.…”
Section: Figurementioning
confidence: 93%
See 1 more Smart Citation
“…For example, results from one study that compared the bleeding profiles of high-and lowdose combinations of HT showed cumulative amenorrhea rates that were lower compared with placebo at all time points for up to 1 year with all dose combinations (25), as similarly shown in previous reports (29). In a study comparing tibolone versus low-dose continuous combined E 2 plus norethisterone acetate (26), bleeding rates of 18.3% and 33.1%, respectively, during the first 3-month interval of treatment decreased to 11.4% and 19.9%, respectively, during the interval from month 7 through 9. Bleeding profiles associated with other nontraditional HT approaches may not be as favorable.…”
Section: Figurementioning
confidence: 93%
“…The mean number of bleeding or spotting days with these BZA/CE doses was not significantly different from placebo over 2 years of therapy. Irregular bleeding with HT is a key contributor to discontinuation of therapy and one of the most common side effects within the first 3 months of treatment (26). However, a randomized, placebo-controlled trial (25) that evaluated bleeding profiles of postmenopausal women receiving HT found that irregular bleeding and spotting gradually decreased over the first year of treatment.…”
Section: Figurementioning
confidence: 99%
“…The biological actions of tibolone are mediated through the metabolites of tibolone (3 -OH-tibolone, 3 -OH-tibolone, and Δ 4 -isomer) by binding estrogen or progesterone receptors in multiple target tissues and organs (brain, bone, breast, and endometrium). Based on several randomized trials, tibolone has shown comparable effects with traditional estrogen therapy (ET)/HT on relieving vasomotor symptoms/ genital atrophy, improving the quality of life, and preventing bone loss in postmenopausal women [81][82][83][84]. Currently 4 studies have shown the effects of tibolone on BW or body composition in postmenopausal women.…”
Section: Postmenopausal Hormone Therapy and Change In Body Compositionmentioning
confidence: 99%
“…7 There are some safety and tolerability concerns with EPT, including an increased risk of venous thromboembolic events (VTEs), stroke, and potentially breast cancer, as well as irregular vaginal bleeding and breast tenderness. [7][8][9][10] Other than EPT, most pharmacologic menopausal treatment options are therapies targeted to either menopausal symptoms or the prevention or treatment of osteoporosis. Nonprescription remedies, such as soy-based isoflavones, have been reported in some studies to provide moderate menopausal symptom relief but have been shown in other studies to be comparable to placebo (PBO).…”
Section: Introductionmentioning
confidence: 99%